Propagação de trincas nos modelos de Hudson e de Forman-Newman-de Koning, via método "Fast Crack Bounds" - Machado Junior, Waldir Mariano (2019)
In general, a significant part of the life of a mechanical component occurs, the crack propagation stage in fatigue. The Linear Elastic Fracture Mechanics (LEFM) presents several evolutionary models that try to predict life under fatigue. These models are classified into: under constant amplitude loading (CAL) and under variable amplitude loading (VAL). In general, some of these crack propagation models can be formulated as an initial value problem (IVP). This wok presented the extension and adequacy of the "Fast Crack Bounds" (FCB) method for the establishment of the upper and lower bounds functions for models of evolution from crack size to variable loading. The models studied were those of Hudson and Forman-Newman-De Koning (FNK). These models were delimited according to the following criteria: region of coverage of the model, that is, region I to III; simplicity and diffusion. An application was also made to obtain an approximate numerical solution, from the arithmetic mean of the upper and lower bounds obtained in the method applied in this work, when the law of evolution is not known. The performance of the FCB method was measured by the functions of the relative deviation, the relative errors of the means of the bounds functions and the ratio of the computational times in relation to the numerical solution by the fourth order Runge-Kutta (RK4) method, compared to the experimental results found in the works of Chang (1981), Gróza and Váradi (2017) and Dirik and Yalçinkaya (2016). It was observed, for the models studied, that the FCB method presents a satisfactory approximation of the behavior of the evolution of the crack.